Evaluation of Groundwater Pollution Caused by Leakage of Leachate Produced Landfill using Numerical Model - Mohsen Azizi; Abbas Khashei; Mehdi Dastorani (Mashhad University of Medical Sciences, 2017)
Background & objective: Today, the pollution caused by landfills is considered as one the serious environmental threats, including groundwater resources. The purpose of this research, the use of mathematical models and numerical with high precision in determining and explaining the current situation and relatively accurate predictions, to examine the groundwater pollution caused by leakage of leachate centers around landfill. Materials & Methods: In this research, The MODFLOW, MODPATH and MT3DMS models was used to estimate the speed of movement of pollution, tracing path and simulate the process of transfer of leachate producedat San Angelo landfill site in the United States to the downstream drinking water well. Also Three scenarios of a) improved bedding of landfill bottom and reduced leachate penetration to 25%; b) Reducing the amount of extraction downstream drinking water well to 20%; c) landfill Movement as much as 100m to upstream were evaluated. Results: The results of the modeling showed that in the current situation, the leachate produced landfill reaches the downstream well going through a distance of 608 meters in 2158 days. By applying three scenarios in the numerical model was seen that the leachate reaches to the downstream well by passing a distance of 613, 618, and 667 m in 4000, 3250 and 4000 days, respectively. Conclusion: Therefore, in the field of locating the landfill and leakage of leachateto groundwater, numerical models can be used to predict the direction and speed of pollution movement and to make management decisions for reducing the time and distance of arriving the pollution at the groundwater.